Preparation method and application of MnO2 / montmorillonite composite material for catalyzing formaldehyde degradation
Through the composite of MnO2 and montmorillonite and the synergistic effect of potassium ions, an efficient catalyst was prepared, which solved the problem of low efficiency of catalytic formaldehyde degradation of existing materials at room temperature, and achieved efficient, stable and low-cost catalysis. Effect.
Patent Information
- Application Number
- CN202411567200.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-05
AI Technical Summary
Existing room temperature catalytic materials are inefficient, have poor stability, high cost when catalyzing formaldehyde degradation, and are difficult to be widely used in indoor air pollution control.
By combining MnO2 with montmorillonite, a MnO2/montmorillonite composite material was prepared by using the synergistic exchange capacity of montmorillonite and the synergistic effect of potassium ions. This material forms manganese-rich MnO2 through the warming reaction of ammonium oxalate, which improves the reaction activity and stability of the catalyst.
The formaldehyde oxidation reaction activity of the catalyst under room temperature conditions is significantly improved, the cost of material preparation and application is reduced, and the stability and efficiency of the catalyst are improved.
Smart Images

Figure BDA0005119556010000101 
Figure BDA0005119556010000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of mineral composite catalytic materials, and in particular to a preparation method and application of a MnO2 / montmorillonite composite material for catalyzing formaldehyde degradation. Background Art
[0002] Formaldehyde is the main pollutant in indoor air. The sources of indoor formaldehyde are wide and the cycle is long, making it difficult to cure it from the source. At present, indoor formaldehyde pollution strategies can be mainly divided into three types: source pollution control, daily ventilation and end-of-pipe treatment. The end-of-pipe treatment technologies mainly include physical adsorption, chemical adsorption, thermal catalysis, photocatalysis, etc. The adsorption method only transfers pollutants from the gas phase to the solid phase, and does not achieve true removal, and there is a problem of adsorption saturation and desorption; currently, most photocatalytic materials represented by nano-TiO2 on the market can only use ultraviolet light, artificial light sources are costly and have limited service life, and the photocatalytic oxidation efficiency is usually low, making it difficult to be applied on a large scale in the field of indoor air pollution control; although thermal catalytic technology is efficient, the activation of lattice oxygen often requires high temperature, and the excessively high application temperature makes it difficult to be applied on a large scale in indoor environments. In recent years, room temperature catalytic oxidation technology has been considered the most promising indoor formaldehyde purification technology due to its mild reaction conditions and the lack of additional energy, but existing room temperature catalytic materials generally have problems such as low efficiency, poor stability and high cost.
[0003] Transition metal oxides have great potential for low-temperature oxidation of formaldehyde due to their surface acid-base properties and redox properties. Among them, manganese oxides have high catalytic activity, good thermal stability, low toxicity and up to 30 different crystal structures. They are currently the most widely studied transition metal catalysts. Studies have shown that the pore size (determines the adsorption of formaldehyde in the pore), redox properties and average valence state of manganese in manganese dioxide with different pore structures are key factors determining the formaldehyde oxidation performance. The mechanism of MnO2 oxidation of formaldehyde at room temperature is as follows: formaldehyde adsorbed on the surface of MnO2 is oxidized to formic acid and carbonate under the action of surface hydroxyl groups, and formic acid is further oxidized to carbon dioxide and water by hydroxyl groups. Carbonate will compete with water vapor on the surface for adsorption and slowly fall off. The surface hydroxyl groups consumed in this process are regenerated by the reaction of surface active oxygen and water vapor. The process from the intermediate product formate to carbonate or carbon dioxide in this process is the rate-limiting step of the entire formaldehyde oxidation, and the high-speed regeneration of hydroxyl groups can accelerate this step; therefore, the more hydroxyl groups on the surface of MnO2 at room temperature, the higher its activity and the faster the rate of adsorption of formaldehyde. At the same time, the abundance of surface active oxygen also determines the regeneration rate of surface hydroxyl groups. Surface active oxygen species can be continuously formed by the dissociation of oxygen in the air through the action of surface lattice oxygen under the action of oxygen vacancies. Therefore, the mobility of oxygen species and the abundance of lattice oxygen play an important role in the purification process.
[0004] Montmorillonite is a natural clay mineral with cation exchange capacity, which is widely available and inexpensive. Montmorillonite has a strong dispersibility in water. Introducing montmorillonite as a carrier in the synthesis process of MnO2 can make MnO2 uniformly loaded on the montmorillonite sheet through cation exchange and mineral carrier confinement effect, which can effectively solve the problem of MnO2 being easy to agglomerate, difficult to recycle and high cost. In addition, the introduction of potassium ions can also cooperate with MnO2 to catalyze the degradation of formaldehyde, and the presence of potassium ions can also improve O latt , O ads , Mn 3+ and Mn 4+ The generation of a large number of oxygen vacancies enhances the mobility of lattice oxygen and promotes the activation of molecular oxygen, so that there are more active oxygen on manganese oxide, which theoretically further enhances the ability of MnO2 to catalyze the oxidation of formaldehyde at room temperature. Summary of the invention
[0005] The purpose of the present invention is to provide a preparation method and application of a MnO2 / montmorillonite composite material for catalyzing formaldehyde degradation. Compared with existing manganese oxides, the MnO2 / montmorillonite composite material prepared by the present invention effectively improves the reaction activity of the catalyst in catalytic oxidation of formaldehyde at room temperature and reduces the cost of material preparation and application.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A method for preparing a MnO2 / montmorillonite composite material for catalyzing formaldehyde degradation comprises the following steps:
[0008] S1: After montmorillonite is evenly dispersed in water, potassium salt is added and blended, and then washed, centrifuged and dried to obtain potassium-based montmorillonite;
[0009] S2: After mixing potassium-based montmorillonite and water, potassium permanganate is added and dispersed evenly to obtain a mixed solution;
[0010] S3: Add ammonium oxalate to the mixed solution obtained in S2, heat the mixture to react, filter and wash until neutral, and dry to obtain a MnO2 / montmorillonite composite material.
[0011] As a further embodiment of the present invention: the montmorillonite is a sodium-based montmorillonite having a cation exchange capacity greater than 100 mmol / 100 g.
[0012] As a further embodiment of the present invention: the potassium salt is any one of potassium chloride, potassium hydroxide, potassium acetate, potassium oxalate and potassium hydrogen oxalate or a mixture of any of the above.
[0013] As a further solution of the present invention: the addition ratio of montmorillonite to potassium salt in S1 is: 0.02-0.04 mol of potassium salt is mixed with every 100 g of montmorillonite.
[0014] As a further solution of the present invention: the mass ratio of potassium-montmorillonite to potassium permanganate in S2 is 0.5-5g:3.636g.
[0015] As a further embodiment of the present invention: the molar ratio of ammonium oxalate in S3 to permanganate in the mixed solution is 1:1-3.
[0016] As a further solution of the present invention: the specific steps of the temperature raising reaction in S3 are: raising the temperature to 45-95°C and keeping the temperature under stirring for 6-20 hours.
[0017] As a further solution of the present invention: the specific steps of the temperature raising reaction in S3 are: raising the temperature to 65-95°C and keeping the temperature under stirring for 10-14h.
[0018] The MnO2 / montmorillonite composite material prepared by any of the above preparation methods is used for catalytic degradation of formaldehyde.
[0019] Beneficial effects of the present invention:
[0020] The present invention uses montmorillonite, potassium salt, potassium permanganate and ammonium oxalate as main raw materials to prepare a MnO2 / montmorillonite composite material which can significantly improve the catalytic degradation effect of formaldehyde at room temperature. The present invention first utilizes the cation exchange function of montmorillonite to mix and disperse montmorillonite and potassium salt, and introduces potassium permanganate into the interlayer or surface of montmorillonite in advance. + , get K + Modified potassium-montmorillonite, namely potassium-montmorillonite; the present application uses potassium-montmorillonite as a carrier and provides a solid potassium source in the subsequent reaction, and potassium permanganate provides a manganese source. By adding ammonium oxalate, the manganese defects in the manganese dioxide crystals are controlled and reduced to obtain a manganese-rich MnO2 / montmorillonite composite material.
[0021] The potassium ions in the potassium-based montmorillonite prepared in the present application act synergistically to adjust the electronic properties of the loaded manganese oxide, causing lattice distortion of the manganese oxide, thereby enhancing the mobility of lattice oxygen and increasing the abundance of surface active oxygen; so that the manganese dioxide crystals can be evenly loaded into the montmorillonite layer structure and the potassium ions loaded by the montmorillonite can be effectively adsorbed on the manganese defect sites. The MnO2 / montmorillonite composite material prepared in the present application has the characteristics of excellent abundance of surface hydroxyl groups and active lattice oxygen and fast mobility of active oxygen species.
[0022] The MnO2 / montmorillonite composite material prepared by the present invention is used as a material for catalytic degradation of formaldehyde. Compared with the existing manganese oxide, it effectively improves the reaction activity of the catalyst for catalytic oxidation of formaldehyde at room temperature and reduces the cost of material preparation and application. It has the advantages of simple production process, low cost, high catalytic efficiency, etc. DETAILED DESCRIPTION
[0023] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] Example 1 A method for preparing a MnO2 / montmorillonite composite material for catalyzing formaldehyde degradation comprises the following steps:
[0025] S1: After 10 g of montmorillonite is evenly dispersed in water, 2.94 g (0.03 mol) of potassium acetate is added and blended, and then washed, centrifuged and dried to obtain potassium-based montmorillonite;
[0026] S2: After mixing 2 g potassium-montmorillonite and 100 mL water, 3.636 g (0.023 mol) potassium permanganate was added and dispersed evenly, and 1.141 g (0.009 mol) ammonium oxalate was added and mixed, and the temperature was raised to 90°C, and the reaction was kept warm for 12 hours. The mixture was filtered and washed until neutral to remove impurities, and dried at 70°C to obtain a MnO2 / montmorillonite composite material.
[0027] Example 2 A method for preparing a MnO2 / montmorillonite composite material for catalyzing formaldehyde degradation comprises the following steps:
[0028] S1: After 10 g of montmorillonite is evenly dispersed in water, 2.94 g (0.03 mol) of potassium acetate is added and blended, and then washed, centrifuged and dried to obtain potassium-based montmorillonite;
[0029] S2: After mixing 2 g potassium-montmorillonite and 100 mL water, add 3.636 g (0.023 mol) potassium permanganate and disperse evenly, add 1.426 g (0.011 mol) ammonium oxalate and mix, heat to 90 ° C, keep the reaction for 12 hours, filter and wash until neutral to remove impurities, and dry at 70 ° C to obtain a MnO2 / montmorillonite composite material.
[0030] Example 3 A method for preparing a MnO2 / montmorillonite composite material for catalyzing formaldehyde degradation comprises the following steps:
[0031] S1: After 10 g of montmorillonite is evenly dispersed in water, 2.94 g (0.03 mol) of potassium acetate is added and blended, and then washed, centrifuged and dried to obtain potassium-based montmorillonite;
[0032] S2: After mixing 2 g potassium-montmorillonite and 100 mL water, 3.636 g (0.023 mol) potassium permanganate was added and dispersed evenly, and 0.951 g (0.008 mol) ammonium oxalate was added and mixed, and the temperature was raised to 90°C, and the reaction was kept warm for 12 hours. The mixture was filtered and washed until neutral to remove impurities, and dried at 70°C to obtain a MnO2 / montmorillonite composite material.
[0033] Example 4 A method for preparing a MnO2 / montmorillonite composite material for catalyzing formaldehyde degradation comprises the following steps:
[0034] S1: After 10 g of montmorillonite is evenly dispersed in water, 2.24 g (0.03 mol) of potassium chloride is added and mixed, and the mixture is washed, centrifuged and dried to obtain potassium-based montmorillonite;
[0035] S2: After mixing 2 g potassium-montmorillonite and 100 mL water, 3.636 g (0.023 mol) potassium permanganate was added and dispersed evenly, and 1.141 g (0.009 mol) ammonium oxalate was added and mixed, and the temperature was raised to 90°C, and the reaction was kept warm for 12 hours. The mixture was filtered and washed until neutral to remove impurities, and dried at 70°C to obtain a MnO2 / montmorillonite composite material.
[0036] Example 5 A method for preparing a MnO2 / montmorillonite composite material for catalyzing formaldehyde degradation comprises the following steps:
[0037] S1: After 10 g of montmorillonite is evenly dispersed in water, 1.68 g (0.03 mol) of potassium hydroxide is added and blended, and then washed, centrifuged and dried to obtain potassium-based montmorillonite;
[0038] S2: After mixing 2 g potassium-montmorillonite and 100 mL water, 3.636 g (0.023 mol) potassium permanganate was added and dispersed evenly, and 1.141 g (0.009 mol) ammonium oxalate was added and mixed, and the temperature was raised to 90°C, and the reaction was kept warm for 12 hours. The mixture was filtered and washed until neutral to remove impurities, and dried at 70°C to obtain a MnO2 / montmorillonite composite material.
[0039] Example 6 A method for preparing a MnO2 / montmorillonite composite material for catalyzing formaldehyde degradation comprises the following steps:
[0040] S1: After 10 g of montmorillonite is evenly dispersed in water, 5.53 g (0.03 mol) of potassium oxalate is added and mixed, and the mixture is washed, centrifuged and dried to obtain potassium-based montmorillonite;
[0041] S2: After mixing 2 g potassium-montmorillonite and 100 mL water, 3.636 g (0.023 mol) potassium permanganate was added and dispersed evenly, and 1.141 g (0.009 mol) ammonium oxalate was added and mixed, and the temperature was raised to 90°C, and the reaction was kept warm for 12 hours. The mixture was filtered and washed until neutral to remove impurities, and dried at 70°C to obtain a MnO2 / montmorillonite composite material.
[0042] Example 7 A method for preparing a MnO2 / montmorillonite composite material for catalyzing formaldehyde degradation comprises the following steps:
[0043] S1: After 10 g of montmorillonite is evenly dispersed in water, 2.94 g (0.03 mol) of potassium acetate is added and blended, and then washed, centrifuged and dried to obtain potassium-based montmorillonite;
[0044] S2: After mixing 2 g potassium-montmorillonite and 100 mL water, 3.636 g (0.023 mol) potassium permanganate was added and dispersed evenly, and 1.141 g (0.009 mol) ammonium oxalate was added and mixed, and the temperature was raised to 65°C, and the reaction was kept warm for 12 hours. The impurities were removed by filtration and washing until neutral, and the mixture was dried at 70°C to obtain a MnO2 / montmorillonite composite material.
[0045] Example 8 A method for preparing a MnO2 / montmorillonite composite material for catalyzing formaldehyde degradation comprises the following steps:
[0046] S1: After 10 g of montmorillonite is evenly dispersed in water, 2.94 g (0.03 mol) of potassium acetate is added and blended, and then washed, centrifuged and dried to obtain potassium-based montmorillonite;
[0047] S2: After mixing 2 g potassium-montmorillonite and 100 mL water, 3.636 g (0.023 mol) potassium permanganate was added and dispersed evenly, and 1.141 g (0.009 mol) ammonium oxalate was added and mixed, and the temperature was raised to 95°C, and the reaction was kept warm for 12 hours. The mixture was filtered and washed until neutral to remove impurities, and dried at 70°C to obtain a MnO2 / montmorillonite composite material.
[0048] Example 9 A method for preparing a MnO2 / montmorillonite composite material for catalyzing formaldehyde degradation comprises the following steps:
[0049] S1: After 10 g of montmorillonite is evenly dispersed in water, 2.94 g (0.03 mol) of potassium acetate is added and blended, and then washed, centrifuged and dried to obtain potassium-based montmorillonite;
[0050] S2: After mixing 2 g potassium-montmorillonite and 100 mL water, 3.636 g (0.023 mol) potassium permanganate was added and dispersed evenly, and 1.141 g (0.009 mol) ammonium oxalate was added and mixed, and the temperature was raised to 90°C, and the reaction was kept warm for 10 hours. The mixture was filtered and washed until neutral to remove impurities, and dried at 70°C to obtain a MnO2 / montmorillonite composite material.
[0051] Example 10 A method for preparing a MnO2 / montmorillonite composite material for catalyzing formaldehyde degradation comprises the following steps:
[0052] S1: After 10 g of montmorillonite is evenly dispersed in water, 2.94 g (0.03 mol) of potassium acetate is added and blended, and then washed, centrifuged and dried to obtain potassium-based montmorillonite;
[0053] S2: After mixing 2 g potassium-montmorillonite and 100 mL water, 3.636 g (0.023 mol) potassium permanganate was added and dispersed evenly, and 1.141 g (0.009 mol) ammonium oxalate was added and mixed, and the temperature was raised to 90°C, and the reaction was kept warm for 14 hours. The impurities were removed by filtration and washing until neutral, and the mixture was dried at 70°C to obtain a MnO2 / montmorillonite composite material.
[0054] Example 11 A method for preparing a MnO2 / montmorillonite composite material for catalyzing formaldehyde degradation comprises the following steps:
[0055] S1: After 10 g of montmorillonite is evenly dispersed in water, 2.94 g (0.03 mol) of potassium acetate is added and blended, and then washed, centrifuged and dried to obtain potassium-based montmorillonite;
[0056] S2: After mixing 4.667 g potassium-montmorillonite and 100 mL water, 3.636 g (0.023 mol) potassium permanganate was added and dispersed evenly, and 1.141 g (0.009 mol) ammonium oxalate was added and mixed, and the temperature was raised to 90°C, and the reaction was kept warm for 12 hours. The impurities were removed by filtration and washing until neutral, and the mixture was dried at 70°C to obtain a MnO2 / montmorillonite composite material.
[0057] Example 12 A method for preparing a MnO2 / montmorillonite composite material for catalyzing formaldehyde degradation, comprising the following steps:
[0058] S1: After 10 g of montmorillonite is evenly dispersed in water, 2.94 g (0.03 mol) of potassium acetate is added and blended, and then washed, centrifuged and dried to obtain potassium-based montmorillonite;
[0059] S2: After mixing 0.857 g potassium-montmorillonite and 100 mL water, 3.636 g (0.023 mol) potassium permanganate was added and dispersed evenly, and 1.141 g (0.009 mol) ammonium oxalate was added and mixed, and the temperature was raised to 90°C, and the reaction was kept warm for 12 hours. The impurities were removed by filtration and washing until neutral, and the mixture was dried at 70°C to obtain a MnO2 / montmorillonite composite material.
[0060] Comparative Example 1 A method for preparing a MnO2 material for catalyzing formaldehyde degradation comprises the following steps:
[0061] Disperse 100 mL of water and 3.636 g (0.023 mol) of potassium permanganate evenly, add 1.141 g (0.009 mol) of ammonium oxalate and mix, heat to 90°C, keep warm for 12 hours, filter and wash until neutral to remove impurities, dry at 70°C to obtain MnO2 material.
[0062] Comparative Example 2 A method for preparing a MnO2 material for catalyzing formaldehyde degradation comprises the following steps:
[0063] After mixing 2 g of montmorillonite and 100 mL of water, 3.636 g (0.023 mol) of potassium permanganate was added and dispersed evenly. After adding 1.141 g (0.009 mol) of ammonium oxalate and mixing, the temperature was raised to 90°C, and the reaction was kept warm for 12 hours. The impurities were removed by filtration and washing until neutral, and the MnO2 material was dried at 70°C.
[0064] Comparative Example 3 A method for preparing a MnO2 / activated carbon composite material for catalyzing formaldehyde degradation comprises the following steps:
[0065] S1: After 10 g of activated carbon is evenly dispersed in water, 2.94 g (0.03 mol) of potassium acetate is added and blended, washed, centrifuged and dried to obtain potassium-based activated carbon;
[0066] S2: After mixing 2 g potassium-based activated carbon and 100 mL water, add 3.636 g (0.023 mol) potassium permanganate and disperse evenly, add 1.141 g (0.009 mol) ammonium oxalate and mix, heat to 90°C, keep warm for 12 hours, filter and wash until neutral to remove impurities, and dry at 70°C to obtain a MnO2 / activated carbon composite material.
[0067] Comparative Example 4: Commercially available activated carbon.
[0068] Comparative Example 5: Commercially available manganese dioxide formaldehyde removal product.
[0069] Performance Testing
[0070] 1. Formaldehyde degradation performance test
[0071] 1. Instruments and Equipment
[0072] Reaction box: Dimensions are 50×50×50cm, with built-in fan, heating plate, object holder, and temperature sensor.
[0073] Micro syringe: specification is 25μL, accuracy is 0.1μL.
[0074] Infrared photoacoustic spectrometer: can monitor formaldehyde and carbon dioxide concentrations in real time.
[0075] 2. The detection method is in accordance with the national standard GB / T 16129-1995 "Standard method for hygienic examination of formaldehyde in the atmosphere of residential areas - spectrophotometry", and the carbon dioxide concentration in the reactor is monitored in real time by an infrared photoacoustic spectrometer.
[0076] 3. Test steps
[0077] 3.1 Weigh 0.5 g of the catalysts prepared in Examples 1-12 and Comparative Examples 1-3 and spread them evenly on glass vessels and place them on the temperature sensor. Then, inject 2.5 μL of formaldehyde solution onto the heating plate of the sealed box and seal the box.
[0078] 3.2 Turn on the heating plate, infrared photoacoustic spectrometer and fan. After the formaldehyde solution has completely evaporated, turn off the heating plate and start the first sampling. The infrared photoacoustic spectrometer continuously detects the carbon dioxide concentration in the reaction chamber.
[0079] 3.3 After reacting for 3 hours at a temperature of 26°C and a relative humidity of 40% Rh, take a second sample and record the carbon dioxide concentration measured by an infrared photoacoustic spectrometer.
[0080] 4. Data processing
[0081] The removal rate is calculated according to formula (1):
[0082] X1=[1-(C2 / C1)]×100% (1)
[0083] Where:
[0084] X1-removal rate, %;
[0085] C1-initial concentration of formaldehyde, in milligrams per cubic meter (mg / m 3 );
[0086] C2-final formaldehyde concentration, in milligrams per cubic meter (mg / m 3 );Test data are shown in Table 1-2.
[0087] The conversion rate is calculated according to formula (2):
[0088] X2=[(C4-C3) / C1]×100% (2)
[0089] Where:
[0090] X2-conversion rate, %;
[0091] C1-initial concentration of formaldehyde, in milligrams per cubic meter (mg / m 3 );
[0092] C3-initial concentration of carbon dioxide, in milligrams per cubic meter (mg / m 3 );
[0093] C4- final concentration of carbon dioxide, in milligrams per cubic meter (mg / m 3 );Test data are shown in Table 1-2.
[0094] Table 1: Statistical table of formaldehyde degradation performance test data of Examples 1-12 and Comparative Examples 1-3
[0095]
[0096]
[0097] The manganese defect contents in Comparative Example 2, Example 2, Example 3, and Example 1 increase successively. Comparative Example 2 is δ-MnO2 / MMT with a theoretical loading of 50% (not regulated by potassium ions), and Examples 2, 3, and 1 are all regulated by potassium ions. It can be seen from Table 1 that the more manganese defects there are, the higher the formaldehyde removal rate and conversion rate.
[0098] Comparative Example 2, Example 1, Example 4, Example 5, and Example 6 are montmorillonite, montmorillonite pretreated with potassium acetate, montmorillonite pretreated with potassium chloride, montmorillonite pretreated with potassium hydroxide, and montmorillonite pretreated with potassium oxalate, respectively; it can be seen from Table 1 that after the montmorillonite is modified with potassium ions, the formaldehyde removal rate is significantly improved, and the use of different potassium salts to modify montmorillonite has similar effects on the formaldehyde removal rate, while the formaldehyde conversion rate is improved to varying degrees due to different potassium salts. Among them, potassium acetate-modified montmorillonite has the strongest effect on improving the formaldehyde conversion rate. Studies have shown that K + The presence of K enhances the redox properties of Mn and promotes the catalytic activity by enhancing the mobility of lattice oxygen and maintaining the availability of surface active oxygen to sustain the reaction. + The presence of K enhances the activity and mobility of lattice oxygen by weakening the Mn-O bond in manganese oxide and promotes the redox performance of the catalyst. + The increase in K content leads to more Mn vacancies to achieve charge balance. + It can increase the average oxidation state (AOS) value of Mn and the proportion of surface adsorbed oxygen, improve the reducing ability of oxygen species, and promote the formation of formate and carbonate in the HCHO oxidation reaction. Finally, adding K to MnO2 +It can generate more lattice oxygen, surface adsorbed oxygen, and Mn 3+ and Mn 4+ , thereby promoting its redox properties and improving its catalytic ability.
[0099] Comparative Example 3 uses potassium-based activated carbon obtained by treating activated carbon with potassium acetate as a carrier; Example 1 uses potassium-based montmorillonite obtained by treating montmorillonite with potassium acetate as a carrier; + It can promote MnO2 to generate more lattice oxygen, surface adsorbed oxygen, and Mn 3+ and Mn 4+ , improving the material's catalytic degradation ability of formaldehyde.
[0100] Examples 7, 8, 9 and 10 show that too low or too high a reaction temperature, or too short or too long a reaction time, will affect the formation of manganese dioxide crystals in the montmorillonite carrier and the regulation effect of potassium ions, which is not conducive to improving the removal rate and conversion rate of formaldehyde.
[0101] Table 2: Statistical table of formaldehyde degradation performance test data of Example 1, Comparative Examples 1-2, Comparative Examples 4-5
[0102] Formaldehyde removal rate / (%) Formaldehyde conversion rate / (%) Example 1 94.34 76.82 Comparative Example 1 83.70 62.50 Comparative Example 2 77.09 55.29 Comparative Example 4 56.32 0 Comparative Example 5 67.24 59.63
[0103] Comparative Examples 1, 2, 4, and 5 are layered δ-MnO2, MnO2 / MMT with a theoretical loading of 50%, commercially available activated carbon, and a commercially available manganese dioxide formaldehyde removal product, respectively. Experiments show that commercially available activated carbon has no function of degrading formaldehyde. Compared with layered MnO2, the catalyst prepared in Example 1 has significantly better performance than pure MnO2 and commercially available manganese dioxide formaldehyde removal products, indicating that the introduction of montmorillonite carrier significantly improves the catalytic performance of the catalyst and greatly reduces the catalyst preparation cost.
[0104] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A method for preparing a MnO2 / montmorillonite composite material for catalyzing formaldehyde degradation, characterized in that: The steps include: S1: After montmorillonite is evenly dispersed in water, potassium salt is added and blended, and then washed, centrifuged and dried to obtain potassium-based montmorillonite; S2: After mixing potassium-based montmorillonite and water, potassium permanganate is added and dispersed evenly to obtain a mixed solution; S3: Add ammonium oxalate to the mixed solution obtained in S2, heat the mixture to react, filter and wash until neutral, and dry to obtain a MnO2 / montmorillonite composite material.
2. The method for preparing a MnO2 / montmorillonite composite material for catalyzing formaldehyde degradation according to claim 1, characterized in that: The montmorillonite is a sodium-based montmorillonite with a cation exchange capacity greater than 100 mmol / 100 g.
3. The method for preparing a MnO2 / montmorillonite composite material for catalyzing formaldehyde degradation according to claim 1, characterized in that: The potassium salt is any one of potassium chloride, potassium hydroxide, potassium acetate, potassium oxalate and potassium hydrogen oxalate, or a mixture of any of the above.
4. The method for preparing a MnO2 / montmorillonite composite material for catalyzing formaldehyde degradation according to claim 1, characterized in that: The addition ratio of montmorillonite and potassium salt in S1 is: 0.02-0.04 mol of potassium salt is mixed with every 10 g of montmorillonite.
5. The method for preparing a MnO2 / montmorillonite composite material for catalyzing formaldehyde degradation according to claim 1, characterized in that: The mass ratio of potassium montmorillonite to potassium permanganate in S2 is 0.5-5g:3.636g.
6. The method for preparing a MnO2 / montmorillonite composite material for catalyzing formaldehyde degradation according to claim 1, characterized in that: The molar ratio of ammonium oxalate in S3 to permanganate in the mixed solution is 1:1-3.
7. The method for preparing a MnO2 / montmorillonite composite material for catalyzing formaldehyde degradation according to claim 1, characterized in that: The specific steps of the temperature-raising reaction in S3 are: raising the temperature to 45-95° C. and maintaining the temperature for 6-20 hours under stirring conditions.
8. The method for preparing a MnO2 / montmorillonite composite material for catalyzing formaldehyde degradation according to claim 1, characterized in that: The specific steps of the temperature-raising reaction in S3 are: raising the temperature to 65-95° C. and maintaining the temperature for 10-14 hours under stirring conditions.
9. The MnO2 / montmorillonite composite material obtained by the preparation method according to any one of claims 1 to 8 is used for catalytic degradation of formaldehyde.
Citation Information
Patent Citations
Composite air purification catalyst and preparation method thereof
CN106334565A
Preparation method and application of MnO2 catalyst for further mineralizing phenolic waste water at normal temperature
CN108002443A
Manganese-based montmorillonite low-temperature SCR catalyst and preparation method thereof
CN110721674A
Formaldehyde purification material based on natural mineral compounding and preparation method thereof
CN115073065A
Application of birnessite type manganese dioxide in low-temperature catalytic decomposition of methyl mercaptan
CN116253364A